Adherence to International Guidelines for the Treatment of Uncomplicated Urinary Tract Infections in Lebanon - Wissam K. Kabbara; Mohamad M. Meski; Wijdan H. Ramadan; Dina S. Maaliki; Pascale Salameh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. The purpose of this study is to evaluate antibiotic-prescribing practices and adherence to IDSA guidelines for the treatment of uncomplicated urinary tract infections in Lebanon. Methods. This observational prospective study was conducted in 15 community pharmacies in Lebanon over 1 year in adult females. A regimen of nitrofurantoin 100 mg bid for 5 days or fosfomycin 3 grams single dose were considered appropriate. For the bivariate analysis, the chi-square test was used. Results. A total of 376 patients were included in this study. The prescribed antibiotic was appropriate in 35 percent of the patients. Age (more than 50 years) did not significantly affect the appropriateness of the prescribed antibiotic (p=0.508). The frequency of attacks per year (more than 3) negatively affected the choice of antibiotic (p=0.025). The dose and duration of the prescribed antibiotic was appropriate in 73 and 58 percent of the patients, respectively, with a significant inappropriate dose and duration with fluoroquinolones as compared to nitrofurantoin and fosfomycin (p<0.001 for the dose and p=0.014 for the duration of therapy). Conclusions. In an era of increasing bacterial resistance, interventions that improve physicians’ prescribing practices for uncomplicated urinary tract infections are needed.